Lithium ion secondary battery

By pre-containing a specific amount of lithium in the negative electrode composite layer of the lithium ion secondary battery, and using appropriate lithium transition metal oxides in the positive electrode composite layer to adjust the Li/M ratio, the problem of lithium ion escape is solved, and the battery output is improved and the life span is increased.

CN119890401APending Publication Date: 2025-04-25TOYOTA BATTERY CO LTD +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411468627.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-10-24
Filing Date
2024-10-21
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

Existing lithium-ion secondary batteries can easily cause lithium ions to escape during repeated charging and discharging, thereby shortening battery life and unable to meet the needs of high-performance electric vehicles and other uses.

Method used

By pre-containing lithium at 1000 ppm or more and 1500 ppm or less in the negative electrode composite layer, and setting the density of the negative electrode composite layer is 1.1 g/cc or more and 1.4 g/cc or less, combining with the use of lithium transition metal oxide in the positive electrode composite layer, and adjusting the Li/M ratio to 1.16 or more and 1.20 or less, ensuring effective utilization of lithium ions inside the battery.

Benefits of technology

The output of lithium-ion secondary batteries is improved and the service life of the battery is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119890401A_ABST
    Figure CN119890401A_ABST
Patent Text Reader

Abstract

The purpose of the present invention is to improve the battery output and prolong the life of a lithium ion secondary battery. A lithium ion secondary battery is provided with an electrode body in which positive and negative electrode sheets are laminated with a separator interposed therebetween. Each electrode sheet is formed by applying a composite material paste, which is an electrode composite material, to a base material. The facing surface of the negative electrode mixture layer in the negative electrode-side electrode sheet is larger than the facing surface of the positive electrode mixture layer in the positive electrode-side electrode sheet. Furthermore, the negative electrode mixture layer contains lithium in an amount of 1000 ppm or more and 1500 ppm or less, and the density of the negative electrode mixture layer is set to 1.1 g / cc or more and 1.4 g / cc or less. The positive electrode composite material layer contains a lithium transition metal oxide as a positive electrode active material. The Li / M ratio, which is the ratio of the sum of the number of atoms of the transition metal to the number of atoms of lithium, is set to 1.16-1.20.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a lithium ion secondary battery. Background Art

[0002] In the past, the electrode body of a lithium ion secondary battery was formed by, for example, laminating electrode sheets on the positive electrode side and the negative electrode side with a separator. Each of these electrode sheets is formed by applying an electrode composite material to a substrate as a current collector. In such a lithium ion secondary battery, as shown in Patent Document 1, Patent Document 2, etc., the negative electrode composite material constituting the electrode sheet on the negative electrode side is preliminarily made to contain lithium.

[0003] That is, by increasing the amount of lithium in the positive electrode composite material layer of the electrode sheet on the positive electrode side, the battery output of the lithium ion secondary battery can be increased. However, by adopting such a structure, the lithium ions that should have moved between the mutually opposing parts of the positive electrode composite material layer and the negative electrode composite material layer are also easily moved to the non-opposing part of the negative electrode composite material layer that is not opposed to the positive electrode composite material layer. In this way, the lithium in the positive electrode composite material layer escapes to the non-opposing part of the negative electrode composite material layer, which easily promotes the reduction of the battery capacity caused by repeated charging and discharging. That is, the problem of shortened battery life will arise.

[0004] Based on this, in the above-mentioned prior art, the non-opposing portion of the negative electrode composite material layer is preliminarily provided with more lithium than the opposing portion of the negative electrode composite material layer. Thus, the lithium in the positive electrode composite material layer is not easy to escape to the non-opposing portion of the negative electrode composite material layer, thereby achieving an improvement in the battery life of the lithium ion secondary battery. Prior art literature Patent Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2018-056412 Patent Document 2: Japanese Patent Application Laid-Open No. 7-192766 Summary of the invention Problems to be solved by the invention

[0006] However, further improvement of the performance of lithium ion secondary batteries is increasingly being sought in applications such as electric vehicles that require high levels of battery performance. Therefore, further improvements are also required for the above-mentioned prior art to meet the increasing demand for lithium ion secondary batteries. Means for solving problems

[0007] A lithium-ion secondary battery based on one embodiment of the present invention comprises an electrode body formed by stacking electrode sheets on the positive electrode side and the negative electrode side with separators sandwiched between them, wherein each of the electrode sheets is formed by coating an electrode composite material onto a substrate serving as a current collector, and an opposing surface of the negative electrode composite material layer in the electrode sheet on the negative electrode side is larger than an opposing surface of the positive electrode composite material layer in the electrode sheet on the positive electrode side, wherein the negative electrode composite material layer pre-contains lithium in an amount of not less than 1000 ppm and not more than 1500 ppm, and a density of the negative electrode composite material layer is not less than 1.1 g / cc and not more than 1.4 g / cc, and the positive electrode composite material layer contains a lithium transition metal oxide as a positive electrode active material, and a ratio of the sum of the number of atoms of the transition metal (M) in the lithium transition metal oxide to the number of atoms of lithium (Li), i.e., a Li / M ratio, is not less than 1.16 and not more than 1.20.

[0008] In the lithium ion secondary battery, the lithium contained in the negative electrode composite material layer in advance may be derived from the carboxymethyl cellulose-lithium salt contained in the negative electrode composite material that forms the negative electrode composite material layer by the coating.

[0009] In the lithium ion secondary battery, the negative electrode composite material may include 0.4 wt % or more and 0.6 wt % or less of the carboxymethyl cellulose-lithium salt.

[0010] In the above-mentioned lithium-ion secondary battery, the lithium transition metal oxide contained in the above-mentioned positive electrode composite material layer can be LiNi x Co y Mn z O2 [x+y+z=1,0 <x<1,0<y<1,0<z<1]。

[0011] In the lithium ion secondary battery, the ratio of the negative electrode capacity to the positive electrode capacity of the electrode sheets on the positive electrode side and the negative electrode side may be 1.6 or more and 1.8 or less.

[0012] In the lithium ion secondary battery, the end region of the electrode sheet where the electrode composite material is not applied to the substrate is defined as an uncoated portion of the electrode sheet, and the electrode sheet on the negative electrode side may have the end region with a width of the uncoated portion of 300 μm or less.

[0013] In the lithium ion secondary battery, the separator may have a porosity of 50% or more and 60% or less. Effects of the Invention

[0014] According to the present invention, it is possible to improve the battery output and prolong the battery life. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1It is a perspective view of a secondary battery. Figure 2 This is an exploded view of the electrode body. Figure 3 is a side view of a secondary battery. Figure 4 It is an explanatory diagram schematically showing electrode sheets on the positive electrode side and the negative electrode side facing each other with a separator interposed therebetween. Figure 5 This is an explanatory diagram schematically showing electrode sheets on the positive electrode side and the negative electrode side facing each other with a separator interposed therebetween for a secondary battery of a reference example. Figure 6 This is an explanatory diagram schematically showing an electrode sheet having a double-sided laminate structure. Figure 7 This is a table showing the test results of the secondary batteries in a list. Figure 8 It is a graph showing the relationship between the Li / M ratio and the battery output. Fig. 9 This is a graph showing the relationship between the amount of lithium in the negative electrode composite material layer and the degradation rate. Fig.10 This is a graph showing the relationship between the density of the negative electrode composite material layer and the degradation rate. DETAILED DESCRIPTION

[0016] Hereinafter, one embodiment of a secondary battery will be described with reference to the drawings. (Lithium-ion secondary battery) like Figure 1 As shown, the secondary battery 1 includes an electrode body 10 integrating a positive electrode 3, a negative electrode 4 and a separator 5, and a case 20 accommodating the electrode body 10. The secondary battery 1 of this embodiment may be a lithium ion secondary battery in which the electrode body 10 in the case 20 is impregnated with a non-aqueous electrolyte solution (not shown).

[0017] In detail, in the secondary battery 1 of the present embodiment, the positive electrode 3, the negative electrode 4 and the separator 5 have a sheet-like appearance and are stacked with the separator 5 sandwiched between the positive electrode 3 and the negative electrode 4. By winding the stack of the positive electrode 3, the negative electrode 4 and the separator 5, the positive electrode 3 and the negative electrode 4 are alternately arranged in the radial direction of the wound body, forming an electrode body 10.

[0018] The case 20 of this embodiment includes a flat, substantially rectangular box-shaped case body 21 and a lid member 22 that closes an open end 21 x of the case body 21. The electrode body 10 of this embodiment has a flat outer shape corresponding to the box shape of the case 20.

[0019] (Electrode sheet and electrode body) If further details are given, Figure 2 As shown, in the secondary battery 1 of this embodiment, the positive electrode 3 and the negative electrode 4 each include an electrode sheet 35. The electrode sheet 35 includes a current collector 31 having a sheet-like outer shape and an electrode composite material layer 32 laminated on the current collector 31.

[0020] Specifically, for the electrode sheet 35P for the positive electrode 3, an electrode composite material containing a lithium transition metal oxide as a positive electrode active material, that is, a composite material paste 37P as a positive electrode composite material, is applied on a substrate 36P made of aluminum or the like constituting the positive electrode collector 31P. For example, the substrate 36P is a sheet or foil made of a metal such as aluminum. In addition, for the electrode sheet 35N for the negative electrode 4, an electrode composite material in a slurry state containing a carbon-based material as a negative electrode active material, that is, a composite material paste 37N as a negative electrode composite material, is applied on a substrate 36N made of copper or the like constituting the negative electrode collector 31N. For example, the substrate 36N is a sheet or foil made of a metal such as copper. Furthermore, these composite material pastes 37P, 37N each contain a binder. In the secondary battery 1 of the present embodiment, by drying these composite material pastes 37P, 37N, corresponding positive electrode composite material layers 32P and negative electrode composite material layers 32N are formed for the electrode sheets 35P, 35N on the positive electrode side and the negative electrode side, respectively.

[0021] Furthermore, in the secondary battery 1 of the present embodiment, the electrode sheets 35P and 35N on the positive and negative sides are respectively shaped into a strip shape. The electrode body 10 of the present embodiment includes a winding body 10X, which is formed by winding the electrode sheets 35P and 35N on the positive and negative sides stacked with the separator 5 in the width direction ( Figure 2 The winding shaft 10x extending in the left-right direction (in the middle) is wound around it.

[0022] It should be noted that Figure 2 In the embodiment, the separator 5 and the electrode sheets 35P and 35N are wound in such a manner that the electrode sheet 35P constituting the positive electrode 3 is wound inside. Figure 2 1 is an example of the structure of the electrode body 10. In other examples, the separator 5 and the electrode sheets 35P and 35N may be wound in such a manner that the electrode sheet 35N constituting the negative electrode 4 is wound inside. In this way, it is determined whether the electrode sheet 35 disposed on the outermost portion of the electrode body 10 is the electrode sheet 35P constituting the positive electrode 3 or the electrode sheet 35N constituting the negative electrode 4.

[0023] In addition, if Figure 1 to Figure 3As shown, the cover member 22 of the housing 20 is provided with a positive terminal 38P and a negative terminal 38N protruding to the outside of the housing 20. Furthermore, each electrode sheet 35 includes an uncoated portion 39 where the electrode composite material layer 32 is not formed on the collector 31. In the secondary battery 1 of the present embodiment, the electrode sheet 35P constituting the positive electrode 3 is electrically connected to the positive terminal 38P, and the electrode sheet 35N constituting the negative electrode 4 is electrically connected to the negative terminal 38N by utilizing these uncoated portions 39.

[0024] Specifically, the electrode assembly 10 of the present embodiment is arranged such that the winding axis 10x is arranged along the length direction ( Figure 1 The positive electrode 3 is stored in the housing 20 in a state of being in the left-right direction (in the middle) . Furthermore, in this state, the uncoated portion 39P of the electrode sheet 35P constituting the positive electrode 3 is connected to the positive electrode terminal 38P via the connecting member 40P. Similarly, the uncoated portion 39N of the electrode sheet 35N constituting the negative electrode 4 is connected to the negative electrode terminal 38N via the connecting member 40N.

[0025] Then, the electrolyte 45 is injected into the case 20. That is, the electrolyte 45 of the secondary battery 1, which is a lithium ion secondary battery, uses a solution in which a lithium salt as a supporting salt is fused into an organic solvent. Thus, in the secondary battery 1 of this embodiment, the electrolyte 45 is impregnated into the electrode body 10 housed in the case 20.

[0026] (High output and long life) like Figure 4 As shown, in the secondary battery 1 of the present embodiment, when comparing the electrode sheets 35P, 35N on the positive and negative sides constituting the electrode body 10, the negative electrode composite material layer 32N on the negative electrode 4 side is larger than the positive electrode composite material layer 32P on the positive electrode 3 side. In detail, when comparing the positive electrode composite material layer 32P and the negative electrode composite material layer 32N that are opposite to each other with the separator 5 sandwiched therebetween, the opposing surface 50N on the negative electrode composite material layer 32N side is larger than the opposing surface 50P on the positive electrode composite material layer 32P side. If described in further detail, the opposing surface 50N on the negative electrode composite material layer 32N side has a larger area than the opposing surface 50P on the positive electrode composite material layer 32P side. It should be noted that for the sake of convenience of explanation, in Figure 4 and the following references Figure 5 In the figure, the separator 5 is omitted. Thus, the negative electrode mixture layer 32N of the present embodiment includes a facing region 51 facing the positive electrode mixture layer 32P, and a non-facing region 52 not facing the positive electrode mixture layer 32P.

[0027] As described above, the positive electrode composite material layer 32P constituting the electrode sheet 35P on the positive electrode 3 side, that is, the composite material paste 37P as the positive electrode composite material applied to the substrate 36P, contains a lithium transition metal oxide as a positive electrode active material.

[0028] Specifically, in the secondary battery 1 of the present embodiment, the following nickel-cobalt-manganese oxide, which is abbreviated as “NCM”, is used as the lithium transition metal oxide.

[0029] LiNi x Co y Mn z O2 [x+y+z=1,0 <x<1,0<y<1,0<z<1] Furthermore, in the secondary battery 1 of the present embodiment, the ratio of the sum of the number of atoms of the transition metal (M) in the lithium transition metal oxide contained in the positive electrode composite material layer 32P to the number of atoms of lithium (Li), that is, the Li / M ratio is set to be greater than 1.16 and less than 1.20. It should be noted that the Li / M ratio is sometimes referred to as the "Li / Me ratio". In addition, the Li / M ratio is equivalent to the molar ratio in the lithium transition metal oxide. Furthermore, in a general lithium-ion secondary battery, the Li / M ratio is set to, for example, about 1.12 to 1.13. That is, in the secondary battery 1 of the present embodiment, the Li / M ratio is set higher than usual. As a result, in the secondary battery 1 of the present embodiment, more lithium is contained in the positive electrode composite material layer 32P.

[0030] In addition, in the secondary battery 1 of the present embodiment, lithium is also contained in the negative electrode composite material layer 32N of the electrode sheet 35N constituting the negative electrode 4 side. Specifically, in the secondary battery 1 of the present embodiment, before the initial charging of the secondary battery 1, lithium is pre-contained in the negative electrode composite material layer 32N at a level of 1000 ppm or more and 1500 ppm or less. It should be noted that "ppm" in this case means "parts per million by mass". Furthermore, the density of the negative electrode composite material layer 32N is set to be greater than 1.1 g / cc and less than 1.4 g / cc. As a result, the secondary battery 1 of the present embodiment can achieve an increase in output and a longer life.

[0031] To explain in detail, in the secondary battery 1 of the present embodiment, the composite material paste 37N as the negative electrode composite material, which is applied to the substrate 36N to form the electrode sheet 35N on the negative electrode 4 side, contains carboxymethyl cellulose having functions as a thickening material and a dispersing material. It should be noted that the carboxymethyl cellulose is often referred to as "CMC". Furthermore, in the secondary battery 1 of the present embodiment, "CMC-Li" as a lithium salt is used in the "CMC" contained in the composite material paste 37N. It should be noted that in the secondary battery 1 of the present embodiment, the "CMC-Li" is obtained by replacing the cation "Na" of the carboxymethyl cellulose-sodium salt referred to as "CMC-Na" with "Li". Specifically, the composite material paste 37N as the negative electrode composite material of the secondary battery 1 of the present embodiment contains "CMC-Li" in an amount of 0.4wt% or more and 0.6wt% or less. Thus, in the secondary battery 1 of the present embodiment, the amount of lithium contained in the negative electrode mixture layer 32N is set to be 1000 ppm or more and 1500 ppm or less.

[0032] In addition, in the secondary battery 1 of the present embodiment, the negative electrode capacity / positive electrode capacity ratio is set to, for example, 1.6 or more and 1.8 or less for the electrode sheets 35P and 35N constituting the positive electrode side and the negative electrode side of the electrode body 10. It should be noted that the negative electrode capacity / positive electrode capacity ratio in a general lithium-ion secondary battery is, for example, about 1.2 to 1.3. In the secondary battery 1 of the present embodiment, the porosity of the separator 5 is set to, for example, 50% or more and 60% or less.

[0033] (effect) Figure 5 The secondary battery 1B of the reference example shown contains "NCM" as a positive electrode active material in the positive electrode composite material layer 32P, similarly to the secondary battery 1 of the present embodiment. Furthermore, the Li / M ratio of "NCM" is also set to a value higher than usual. Therefore, the secondary battery 1B of the reference example also contains more lithium in the positive electrode composite material layer 32P.

[0034] However, in the secondary battery 1B of the reference example, the negative electrode mixture layer 32N does not contain lithium. The density of the negative electrode mixture layer 32N is also greater than 1.4 g / cc.

[0035] That is, by setting the Li / M ratio high, the positive electrode composite material layer 32P contains more lithium. This can achieve an increase in the output of the secondary battery 1. However, by using such a so-called "positive electrode containing high Li", lithium ions that should have moved from the positive electrode composite material layer 32P to the facing region 51 of the negative electrode composite material layer 32N during charging are also easily moved to the non-facing region 52. As a result, the lithium in the positive electrode composite material layer 32P escapes to the non-facing region 52 of the negative electrode composite material layer 32N, thereby easily promoting the reduction of the battery capacity caused by repeated charging and discharging.

[0036] Regarding this, Figure 4 As shown, in the secondary battery 1 of the present embodiment, lithium is pre-contained in the negative electrode composite material layer 32N including the non-facing region 52. Therefore, even in the case of using a "positive electrode containing high Li", the lithium in the positive electrode composite material layer 32P is not easy to escape to the non-facing region 52 on the negative electrode composite material layer 32N side. In addition, in the secondary battery 1 of the present embodiment, the density of the negative electrode composite material layer 32N is low compared with the secondary battery 1B of the reference example, so the electrolyte 45 easily penetrates into the negative electrode composite material layer 32N. Furthermore, by making the electrolyte 45 permeable to the negative electrode composite material layer 32N in this way, the facing region 51 of the negative electrode composite material layer 32N facing the positive electrode composite material layer 32P is easy to receive lithium ions moved from the positive electrode composite material layer 32P. As a result, the lithium in the positive electrode composite material layer 32P is further difficult to escape to the non-facing region 52 on the negative electrode composite material layer 32N side. As a result, the secondary battery 1 of the present embodiment can achieve an improvement in battery output and a longer life.

[0037] It should be noted that when the Li / M ratio is too high, there is a possibility that the structure of the lithium transition metal oxide "NCM" used in the positive electrode active material cannot be maintained. In addition, by increasing the amount of lithium in the negative electrode composite material layer 32N, the lithium concentration gradient between the positive electrode 3 and the negative electrode 4 is reduced. When the density of the negative electrode composite material layer 32N is low, the permeability of the electrolyte 45 increases, thereby easily promoting the battery reaction of the secondary battery. That is, the deterioration of the secondary battery is also easy to proceed.

[0038] Based on this, in the secondary battery 1 of the present embodiment, as described above, the Li / M ratio on the positive electrode 3 side is set to 1.16 or more and 1.20 or less. In addition, the amount of lithium in the negative electrode composite material layer 32N is set to 1000 ppm or more and 1500 ppm or less. The density of the negative electrode composite material layer 32N is set to a range of 1.1 g / cc or more and 1.4 g / cc or less.

[0039] In addition, "CMC-Li" in the composite material paste 37N as the negative electrode composite material has a function as a thickening material. Therefore, when the content of "CMC-Li" is increased, the viscosity of the composite material paste 37N tends to increase. As a result, the kneading of the composite material paste 37N and the coating of the composite material paste 37N on the substrate 36N become difficult.

[0040] Based on this, in the secondary battery 1 of the present embodiment, as described above, the amount of "CMC-Li" contained in the composite material paste 37N is set to be greater than 0.4wt% and less than 0.6wt%. Furthermore, in the secondary battery 1 of the present embodiment, when the amount of "CMC-Li" contained in the composite material paste 37N is the upper limit value "0.6wt%" of the appropriate range, the amount of lithium contained in the negative electrode composite material layer 32N is the upper limit value "1500ppm" of the appropriate range. As a result, in the secondary battery 1 of the present embodiment, the amount of lithium contained in the negative electrode composite material layer 32N can be easily and accurately adjusted.

[0041] In addition, the negative electrode capacity / positive electrode capacity ratio of the electrode sheets 35P and 35N constituting the positive electrode side and the negative electrode side of the electrode body 10 easily reflects the difference in size between the opposing surface 50N on the negative electrode composite material layer 32N side and the opposing surface 50P on the positive electrode composite material layer 32P side, which are opposite to each other with the separator 5 sandwiched therebetween. That is, usually, by setting the negative electrode capacity / positive electrode capacity ratio high, the non-facing region 52 of the negative electrode composite material layer 32N is expanded. In other words, in the electrode sheet 35N on the negative electrode 4 side, the interval between the uncoated portion 39N sandwiching the non-facing region 52 and the facing region 51 is widened. That is, the uncoated portion 39N on the negative electrode 4 side is spaced apart from the position facing the positive electrode composite material layer 32P as the facing region 51. As a result, the movement of lithium ions from the positive electrode composite material layer 32P toward the uncoated portion 39N on the negative electrode 4 side is suppressed.

[0042] That is, in the secondary battery 1 of the present embodiment, as described above, due to the presence of lithium pre-contained in the negative electrode composite material layer 32N, the lithium in the positive electrode composite material layer 32P is not easy to escape to the non-facing region 52 of the negative electrode composite material layer 32N. Therefore, by setting the negative electrode capacity / positive electrode capacity ratio high, even in the case of expanding the non-facing region 52 of the negative electrode composite material layer 32N, it is not easy to promote the reduction of the battery capacity due to repeated charge and discharge.

[0043] The secondary battery 1 of this embodiment utilizes this feature to avoid lithium precipitation in the uncoated portion 39N on the negative electrode 4 side. By avoiding the occurrence of short-circuit failures caused by lithium precipitation, high safety and reliability can be ensured.

[0044] In addition, if Figure 6 As shown, in the secondary battery 1 of this embodiment, in the electrode sheet 35N disposed on the negative electrode 4 side of the outermost shell of the electrode body 10, only one of the negative electrode composite material layers 32N, 32N stacked on both sides of the substrate 36N is opposite to the positive electrode composite material layer 32P. It should be noted that for the sake of convenience, Figure 6 The description of the electrode sheet 35P on the positive electrode 3 side and the separator 5 is omitted. That is, Figure 6 In the embodiment, the pair of negative electrode composite material layers 32N, 32N are arranged on the radially inner side ( Figure 6 The negative electrode composite material layer 32N (upper side in the middle) becomes the opposing layer 53 facing the positive electrode composite material layer 32P. Figure 6 The negative electrode composite material layer 32N (the lower side in the middle) becomes a non-opposing layer 54 that does not face the positive electrode composite material layer 32P.

[0045] Furthermore, when lithium is not contained in these negative electrode composite material layers 32N, 32N as in the secondary battery 1B of the reference example, there is a possibility that lithium ions bypass the end region 35Nx of the electrode sheet 35N and move from the opposing layer 53 to the non-opposing layer 54. That is, during charging, the opposing layer 53 receives lithium ions from the opposing positive electrode composite material layer 32P, thereby increasing the amount of lithium in the opposing layer 53. In contrast, for the non-opposing layer 54, there is no positive electrode composite material layer 32P in which the amount of lithium is increased. Furthermore, the electrolyte 45 also exists in the end region 35Nx of the electrode sheet 35N. Based on the concentration gradient formed thereby, lithium ions bypass the end region 35Nx and move from the opposing layer 53 to the non-opposing layer 54. As a result, the amount of lithium that can be effectively used decreases, thereby easily promoting the reduction of the battery capacity due to repeated charging and discharging.

[0046] However, in the secondary battery 1 of the present embodiment, lithium is preliminarily contained in both the opposing layer 53 and the non-opposing layer 54. Therefore, even when the amount of lithium in the opposing layer 53 increases due to charging, the concentration gradient between the opposing layer 53 and the non-opposing layer 54 formed in the end region 35Nx of the electrode sheet 35N is small. As a result, in the secondary battery 1 of the present embodiment, lithium ions do not easily move from the opposing layer 53 to the non-opposing layer 54 bypassing the end region 35Nx.

[0047] It should be noted that in the secondary battery 1 of the present embodiment, the electrode sheet 35N on the negative electrode 4 side is located on one side in the width direction of the strip shape wound in the form of the electrode body 10 ( Figure 6 The end region 35Nxa of the substrate 35N is the left side in the figure and has an uncoated portion 39N (see Figure 2). In addition, the electrode sheet 35N is located on the other side in the width direction of the strip shape wound in the form of the electrode body 10 ( Figure 6 The end region 35Nxb (right side in the figure) has a cut portion 55 formed when the electrode sheet 35N is shaped into a strip shape. Furthermore, in the electrode sheet 35N of this embodiment, the cut portion 55 also becomes the uncoated portion 39b where the negative electrode composite material layer 32N is not laminated on the substrate 36N. In the electrode sheet 35N of this embodiment, the width W of the uncoated portion 39b that becomes the cut portion 55 is set to be less than 300 μm.

[0048] That is, the wider the width of the uncoated portion 39 formed in the end region 35Nx of the electrode sheet 35N, the less likely it is that lithium ions will bypass the end region 35Nx and move from the opposing layer 53 toward the non-opposing layer 54. However, in the secondary battery 1 of the present embodiment, as described above, regardless of the presence or absence of the uncoated portion 39, it is not easy for lithium ions to bypass the end region 35Nx and move from the opposing layer 53 toward the non-opposing layer 54. In the secondary battery 1 of the present embodiment, this point is utilized to make the uncoated portion 39b of the end region 35Nxb have a narrow width as described above. As a result, a high degree of design freedom can be ensured for the electrode sheet 35N on the negative electrode 4 side.

[0049] It should be noted that, as a method of suppressing the movement of lithium ions bypassing the end region 35Nx of the electrode sheet 35N from the opposing layer 53 to the non-opposing layer 54, it is considered that the porosity of the separator 5 can also be set low. That is, by adopting such a configuration, the liquid retention of the electrolyte 45 based on the separator 5 is reduced. As a result, the permeability of lithium ions is reduced, and the movement of lithium ions bypassing the end region 35Nx can be suppressed.

[0050] However, when the porosity of the separator 5 is low, the cycle characteristics in the case of repeated charge and discharge are likely to be reduced due to the reduction in the liquid retention of the separator 5. When the liquid retention of the separator 5 is ensured by increasing the porosity of the separator 5, the permeability of lithium ions is improved, thereby easily causing the above-mentioned movement of lithium ions bypassing the end region 35Nx of the electrode sheet 35N.

[0051] In this regard, in the secondary battery 1 of the present embodiment, as described above, by pre-containing lithium in both the opposing layer 53 and the non-opposing layer 54, it is less likely that lithium ions will bypass the end region 35Nx and move from the opposing layer 53 toward the non-opposing layer 54. This can increase the porosity of the separator 5 and improve the cycle characteristics of the secondary battery 1.

[0052] That is, in the secondary battery 1 of the present embodiment, the lower limit of the porosity of the separator 5 is set from the perspective of improving the cycle characteristics. In addition, the upper limit of the porosity is set based on the mechanical strength required of the separator 5. Therefore, in the secondary battery 1 of the present embodiment, as described above, the porosity of the separator 5 is set to a range of 50% or more and 60% or less.

[0053] Next, the effects of this embodiment will be described. (1) A secondary battery 1 as a lithium ion secondary battery has an electrode body 10 in which electrode sheets 35 on the positive electrode side and the negative electrode side are stacked with a separator 5. Each electrode sheet 35 is formed by applying a composite material paste 37 as an electrode composite material to a substrate 36 as a collector 31. In addition, the opposing surface 50N of the negative electrode composite material layer 32N in the electrode sheet 35N on the negative electrode 4 side is larger than the opposing surface 50P of the positive electrode composite material layer 32P in the electrode sheet 35P on the positive electrode 3 side. Furthermore, the negative electrode composite material layer 32N contains lithium in an amount of 1000 ppm or more and 1500 ppm or less, and the density of the negative electrode composite material layer 32N is set to be 1.1 g / cc or more and 1.4 g / cc or less. In addition, the positive electrode composite material layer 32P contains a lithium transition metal oxide as a positive electrode active material. The ratio of the sum of the number of transition metal atoms (M) to the number of lithium atoms (Li) in the lithium transition metal oxide, that is, the Li / M ratio, is set to 1.16 or more and 1.20 or less.

[0054] That is, by setting the Li / M ratio higher, the positive electrode composite material layer 32P contains more lithium. This can achieve an increase in battery output. In addition, by pre-existing lithium in the negative electrode composite material layer 32N including the non-opposing region 52 that is not directly opposite to the positive electrode composite material layer 32P, the lithium in the positive electrode composite material layer 32P is not easy to escape to the non-opposing region 52 of the negative electrode composite material layer 32N. Furthermore, when the density of the negative electrode composite material layer 32N is low, the electrolyte 45 easily penetrates into the negative electrode composite material layer 32N. As a result, the facing region 51 of the negative electrode composite material layer 32N that is directly opposite to the positive electrode composite material layer 32P easily receives lithium ions moved from the positive electrode composite material layer 32P. As a result, the lithium in the positive electrode composite material layer 32P is further less likely to escape to the non-opposing region 52 of the negative electrode composite material layer 32N. Thus, using the above-mentioned structure, it is possible to effectively achieve an increase in battery output and a longer life.

[0055] Furthermore, in the above configuration, there is an advantage that different lithium contents do not need to be set for the facing region 51 and the non-facing region 52. This makes it easy to improve the battery output and extend the battery life.

[0056] (2) The lithium contained in the negative electrode composite material layer 32N in advance comes from the carboxymethyl cellulose-lithium salt contained in the composite material paste 37N which is a composite material paste that is applied to the substrate 36 to form the negative electrode composite material layer 32N.

[0057] That is, for the composite material paste 37N as the negative electrode composite material, carboxymethyl cellulose (CMC) can be used as, for example, a thickening material or a dispersing material. As in the above-mentioned configuration, by using "CMC-Li" as a lithium salt as the "CMC", it is possible to easily form a negative electrode composite material layer 32N containing lithium in advance.

[0058] (3) Composite material paste 37N as the negative electrode composite material contains 0.4 wt % or more and 0.6 wt % or less of carboxymethyl cellulose-lithium salt. By using the above-mentioned structure, the amount of lithium pre-contained in the negative electrode composite material layer 32N can be easily adjusted to the preferred range shown in (1) above. Furthermore, taking into account the viscosity-increasing effect caused by the inclusion of "CMC-Li", the ease of mixing and coating can be ensured. As a result, the battery output can be easily improved and the life can be extended.

[0059] (4) In the positive electrode composite material layer 32P, as a lithium transition metal oxide, LiNi x Co y Mn z O2 [x+y+z=1,0 <x<1,0<y<1,0<z<1]。

[0060] With the above configuration, by setting the Li / M ratio high, the positive electrode mixture layer 32P contains more lithium, thereby improving the battery output.

[0061] (5) The negative electrode capacity / positive electrode capacity ratio of the electrode sheets 35P and 35N on the positive electrode side and the negative electrode side is 1.6 or more and 1.8 or less. That is, the electrode sheet 35N has a portion on the substrate 36N where the negative electrode composite material layer 32N is not provided, that is, an uncoated portion 39N on which the composite material paste 37N is not applied, in its end region 35Nx. In addition, by setting the negative electrode capacity / positive electrode capacity ratio of the electrode sheets 35P and 35N constituting the positive electrode side and the negative electrode side of the electrode body 10 to be high, the non-facing region 52 of the negative electrode composite material layer 32N is expanded. That is, the uncoated portion 39N arranged between the facing region 51 with the non-facing region 52 sandwiched therebetween is spaced from the position facing the positive electrode composite material layer 32P as the facing region 51. Furthermore, by the configuration of (1) above, lithium is preliminarily contained in the non-facing region 52, and thus, even when the non-facing region 52 is large, the lithium in the positive electrode composite material layer 32P is not easily moved to the non-facing region 52. Therefore, according to the above configuration, the battery output can be improved and the life can be extended, and the movement of lithium ions from the positive electrode composite material layer 32P to the uncoated portion 39N on the negative electrode 4 side can be suppressed. Thus, the occurrence of short-circuit failures caused mainly by the precipitation of lithium in the uncoated portion 39N on the negative electrode 4 side can be avoided, thereby ensuring high safety and reliability.

[0062] (6) The electrode sheet 35N on the negative electrode 4 side has the end region 35Nx in which the width W of the uncoated portion 39N is 300 μm or less. That is, in the electrode body 10, one of the pair of negative electrode composite material layers 32N, 32N stacked on both sides of the substrate 36N becomes the opposing layer 53 opposite to the positive electrode composite material layer 32P, and the other may become the non-opposing layer 54 not opposite to the positive electrode composite material layer 32P. Furthermore, in this case, the amount of lithium in the opposing layer 53 increases due to charging, and thus, based on the concentration gradient formed in the end region 35Nx, lithium ions may bypass the end region 35Nx and move from the opposing layer 53 to the non-opposing layer 54. As a result, the amount of lithium that can be effectively used is reduced, and the battery capacity is easily reduced due to repeated charging and discharging.

[0063] However, by the configuration of (1) above, lithium is also included in the non-opposing layer 54 in advance, so that it is not easy for lithium ions to bypass the end region 35Nx and move from the opposing layer 53 to the non-opposing layer 54. This can suppress the reduction in battery capacity due to repeated charge and discharge, and at the same time, as in the above configuration, the uncoated portion 39N of the end region 35Nx has a narrow width, which can ensure a high degree of design freedom.

[0064] (7) The porosity of the separator 5 is 50% or more and 60% or less. The above configuration ensures that the electrolyte 45 retains liquid in the separator 5, and improves the performance change of the secondary battery 1 when charging and discharging are repeated, that is, the cycle characteristics. The separator 5 can ensure sufficient mechanical strength required.

[0065] It should be noted that by improving the liquid retention of the electrolyte 45 based on the separator 5, the permeability of lithium ions is improved. As a result, it is easy for the lithium ions to bypass the end area 35Nx of the electrode sheet 35N and move from the opposing layer 53 to the non-opposing layer 54 as described above. However, by the above-mentioned configuration (1), the non-opposing layer 54 also contains lithium in advance, so it is not easy for such lithium ions to bypass the end area 35Nx and move from the opposing layer 53 to the non-opposing layer 54. This can suppress the reduction in battery capacity caused by repeated charging and discharging.

[0066] It should be noted that the above-mentioned embodiment can be implemented by changing the above-mentioned embodiment as follows: The above-mentioned embodiment and the following modified examples can be implemented by combining with each other within the scope of no technical contradiction.

[0067] In the above embodiment, the lithium contained in the negative electrode composite material layer 32N is derived from the carboxymethyl cellulose-lithium salt contained in the composite material paste 37N, which is a composite material paste that forms the negative electrode composite material layer 32N by coating the substrate 36. However, the present invention is not limited to this, and the method of containing lithium in the negative electrode composite material layer 32N can be changed arbitrarily.

[0068] The lithium transition metal oxide as the positive electrode active material contained in the positive electrode mixture layer 32P is not necessarily limited to the above-mentioned “NCM”, and can be arbitrarily changed. The amount of lithium previously contained in the negative electrode composite material layer 32N can be changed arbitrarily. The density of the negative electrode composite material layer 32N can also be changed arbitrarily. In addition, the Li / M ratio of the lithium transition metal oxide contained in the positive electrode composite material layer 32P can also be changed arbitrarily. However, these values ​​are preferably set within the appropriate range shown in the above embodiment.

[0069] In addition, the amount of carboxymethyl cellulose-lithium salt contained in the composite material paste 37N can be changed arbitrarily. Furthermore, the negative electrode capacity / positive electrode capacity ratio of the electrode sheets 35P and 35N on the positive and negative sides can also be changed arbitrarily. In addition, the porosity of the separator 5 can also be changed arbitrarily. However, these values ​​are also preferably set within the appropriate range shown in the above embodiment.

[0070] In the above-mentioned embodiment, the electrode sheet 35N has a cut-off portion 55 in the end region 35xb when the electrode sheet 35N is shaped into a strip shape, and the cut-off portion 55 has a structure as an uncoated portion 39b. The width W of the uncoated portion 39b is set to be less than 300μm. However, this is not limited to this, and the width W of the uncoated portion 39b can be changed arbitrarily. For example, the width W of the uncoated portion 39b can be "0". In addition, the portion other than the cut-off portion 55 can have an end region 35xb in which the width W of the uncoated portion 39b is less than 300μm.

[0071] Each electrode sheet 35 may have a so-called double-sided laminate structure in which the electrode composite material layer 32 is laminated on both sides of the substrate 36 , or may have a so-called single-sided laminate structure in which the electrode composite material layer 32 is laminated on only one side of the substrate 36 .

[0072] In the above embodiment, the electrode assembly 10 has a structure as a wound body 10X, but the positive electrode side and negative electrode side electrode sheets 35P and 35N stacked with the separator 5 interposed therebetween do not necessarily need to be wound.

[0073] The terminal shapes of the positive terminal 38P and the negative terminal 38N are not limited to Figure 1 The shape shown in FIG. 1 can be changed arbitrarily. Furthermore, the shape of the case 20 as the outer shape of the secondary battery 1 is not necessarily limited to a flat rectangular box shape, and can be changed arbitrarily, for example, to a cylindrical shape. Example

[0074] The following describes examples and the like for further specifying the configuration and effects of the present invention, but the present invention is not limited to these examples. Figure 7 This is a table showing the test results of changing the Li / M ratio of the lithium transition metal oxide contained in the positive electrode composite material layer 32P, the amount of lithium in the negative electrode composite material layer 32N, and the density of the negative electrode composite material layer 32N for the secondary battery 1. In this test, the battery output and battery life were evaluated as the battery performance of the secondary battery 1. As an indicator of battery life, the deterioration rate of the battery capacity was measured. The secondary battery 1 as the object was stored for a specified period of time under a certain temperature environment, and the change in battery capacity before and after storage in this case was measured, thereby measuring the degradation rate.

[0075] It should be noted that Figure 7In the data, the unit of battery output is "W". In addition, the unit of degradation rate is "% / √day". That is, the degradation rate of battery capacity is evaluated by "the reduction rate relative to the square root of the number of days". And, the smaller the value of "% / √day", the slower the degradation rate. That is, it means that the life of the secondary battery 1 as the object of "% / √day" is long.

[0076] The amount of lithium (ppm) in the negative electrode composite material layer 32N was measured as follows. First, an electrode sheet 35N of a specified area is punched out from the electrode sheet 35N as a test piece. Next, the test piece is ultrasonically dispersed in pure water, thereby peeling the negative electrode composite material layer 32N from the substrate 36N. Furthermore, the contents of the dispersed negative electrode composite material layer 32N are dissolved by using nitric acid and hydrogen peroxide. Thereafter, after removing the residue using a membrane filter, the contents of the negative electrode composite material layer 32N are subjected to ICP measurement, thereby quantifying the amount of lithium (ppm). It should be noted that "ICP measurement" is an abbreviation for "high-frequency inductively coupled plasma spectrometry". The measuring device used is "ICPE-9000 manufactured by Shimadzu Corporation".

[0077] The density (g / cc) of the negative electrode mixture layer 32N was measured as follows. First, an electrode sheet 35N of a specified area is punched out from the electrode sheet 35N as a test piece, and the weight of the test piece (the weight of the negative electrode composite material layer 32N and the substrate 36N) is measured. Next, the negative electrode composite material layer 32N is peeled off, and the weight of the substrate 36N portion is measured. Furthermore, the weight of the negative electrode composite material layer 32N portion is subtracted from the weight of the previously measured test piece, thereby measuring the weight of the negative electrode composite material layer 32N portion. Thereafter, the weight of the negative electrode composite material layer 32N portion is divided by the punched-out area of ​​the test piece, thereby calculating the "basis weight (per unit area)". It should be noted that the unit of the "basis weight" is "mg / square centimeter".

[0078] In addition, the thickness of the electrode sheet 35 and the thickness of the substrate 36N were measured using a dot-type film thickness meter. Furthermore, the "thickness of the negative electrode composite material layer 32N" was measured by subtracting the thickness of the substrate 36N from the thickness of the electrode sheet 35. Thereafter, the density (g / cc) of the negative electrode composite material layer 32N was calculated by dividing the above-mentioned "basis weight" by the "thickness of the negative electrode composite material layer 32N".

[0079] The porosity (%) of the separator 5 is measured as follows. First, a long strip of spacer 5 is punched out from the spacer 5, and the weight of the long strip of spacer 5 is measured. It should be noted that, as the weight measurement, "N = 3", that is, three independent measurements are performed. In addition, the theoretical weight is calculated based on the specific gravity of the resin component used in the spacer 5. Thereafter, "weight measurement value (N = 3 average value) / theoretical weight value × 100" is used as the porosity (%) of the spacer 5.

[0080] (Relationship between the amount of lithium in the negative electrode composite material layer and battery output) like Figure 7 and Figure 8 As shown in the test results shown in "Example 1" to "Example 13" and "Comparative Example 1" to "Comparative Example 19" in the table, it is confirmed that the higher the Li / M ratio of the lithium transition metal oxide contained in the positive electrode composite material layer 32P, the higher the battery output. And it is speculated that this tendency is caused by the increase in the amount of lithium in the positive electrode composite material layer 32P as the Li / M ratio increases.

[0081] It should be noted that, when the Li / M ratio is the same, even when the amount of lithium in the negative electrode composite material layer 32N and the density of the negative electrode composite material layer 32N are different, the battery output does not show a significant difference. Figure 8 In the figure, as the battery output tends to increase substantially linearly as the Li / M ratio increases, only the approximate graph α when the lithium amount in the negative electrode mixture layer 32N is "0 ppm" and the density of the negative electrode mixture layer 32N is "1.2 g / cc" is shown.

[0082] (Relationship between negative electrode power and degradation rate) In addition, if Figure 7 and Fig. 9 As shown, according to the test results, it was confirmed that the deterioration rate of the battery capacity tends to be slow due to the increase in the amount of lithium in the negative electrode composite material layer 32N. That is, Fig. 9 The approximate diagram β1 in the figure shows the case where the Li / M ratio is "1.13", and the approximate diagram β2 shows the case where the Li / M ratio is "1.16". In addition, in the figure, the approximate diagram β3 shows the case where the Li / M ratio is "1.18", and the approximate diagram β2 shows the case where the Li / M ratio is "1.20". It should be noted that the density of the negative electrode composite material layer 32N is "1.2g / cc". Moreover, each of these approximate diagrams β1 to β4 shows a tendency that the deterioration rate is optimized to be roughly linear as the amount of lithium in the negative electrode composite material layer 32N increases.

[0083] Specifically, when the Li / M ratio is "1.16" or more, the effect of prolonging the life due to the pre-existence of lithium in the negative electrode composite material layer 32N is more significantly manifested. Furthermore, compared with the case where the amount of lithium in the negative electrode composite material layer 32N is "0ppm", the effect of prolonging the life becomes more significant when the negative electrode composite material layer 32N contains "1000ppm" or more of lithium in advance. According to the test results, it was confirmed that the lower limits of the appropriate ranges shown in the above embodiment, "1.16" and "1000ppm", are respectively appropriate for the Li / M ratio and the amount of lithium pre-contained in the negative electrode composite material layer 32N.

[0084] It should be noted that the approximate graphs β3 and β4 for a higher Li / M ratio show that even when the amount of lithium contained in the negative electrode composite material layer 32N is "600 ppm", the existence of lithium in the negative electrode composite material layer 32N can achieve a sufficient effect of extending the life. Therefore, it is estimated that the lower limit value of the appropriate range of the amount of lithium contained in the negative electrode composite material layer 32N can be expanded to, for example, "600 ppm" or more.

[0085] (Relationship between the density of the negative electrode composite material layer and the degradation rate) In addition, if Figure 7 and Fig.10 As shown, according to the test results, it was confirmed that when the density of the negative electrode composite material layer 32N was "1.4 g / cc" or less, the degradation rate of the battery capacity became slower than when the density was "1.6 g / cc". That is, Fig.10 Approximation diagrams γ1 to γ3 in FIG. 3 respectively show the cases where the amount of lithium previously contained in the negative electrode mixture layer 32N is "0 ppm", "1280 ppm" and "1500 ppm". It should be noted that the Li / M ratio in the positive electrode mixture layer 32P is "1.20".

[0086] Furthermore, regarding these approximate graphs γ1 to γ3, if the density of the negative electrode composite material layer 32N is less than "1.4 g / cc", the deterioration rate becomes faster as the density decreases. It is presumed that this is because, as described above, the permeability of the electrolyte 45 increases, which facilitates the battery reaction, and as a result, the deterioration also easily proceeds.

[0087] In addition, in each of these approximate graphs γ1 to γ3, when the density of the negative electrode composite material layer 32N is "1.1 g / cc" or more, the effect of extending the life is more significantly exhibited. And from this result, it is confirmed that, as shown in the above embodiment, the lower limit value "1.1 g / cc" of the appropriate range of the density of the negative electrode composite material layer 32N is appropriate, and the upper limit value "1.4 g / cc" is appropriate.

[0088] It should be noted that the approximate graphs γ2 and γ3 in the case where lithium is present in the negative electrode composite material layer 32N show that even when the density of the negative electrode composite material layer 32N is "1.0 g / cc", a sufficient effect of extending the life can be obtained. Therefore, it is estimated that the lower limit of the density of the negative electrode composite material layer 32N can also be expanded to "1.0 g / cc" or more.

[0089] (verify) Next, based on Fig. 9 The comparison of “Example 1” to “Example 13” and “Comparative Example 1” to “Example 19” shown in the figure verifies the appropriate ranges of the Li / M ratio, the amount of lithium in the negative electrode composite material layer 32N, and the density of the negative electrode composite material layer 32N.

[0090] In "Example 1" to "Example 3", the Li / M ratio is "1.16" and the density of the negative electrode composite material layer 32N is "1.2 g / cc". Furthermore, regarding the amount of lithium contained in the negative electrode composite material layer 32N, "Example 1" is "1000 ppm", "Example 2" is "1280 ppm", and "Example 3" is "1500 ppm". Therefore, in these "Example 1" to "Example 3", the Li / M ratio, the amount of lithium contained in the negative electrode composite material layer 32N, and the density of the negative electrode composite material layer 32N are all values ​​within the above-mentioned appropriate range.

[0091] When comparing these "Example 1" to "Example 3" with "Comparative Example 1" to "Comparative Example 5" having a Li / M ratio of "1.13", higher battery output was obtained. Regarding the degradation rate of battery capacity, these "Example 1" to "Example 3" showed almost no change compared with "Comparative Example 1" to "Comparative Example 5".

[0092] Furthermore, these "Example 1" to "Example 3" are compared with "Comparative Example 6" and "Comparative Example 7". The Li / M ratio and the density of the negative electrode composite material layer 32N of "Comparative Example 6" and "Comparative Example 7" are equal to those of these "Example 1" to "Example 3". On the other hand, the amount of lithium contained in the negative electrode composite material layer 32N is set to "0 ppm" and "600 ppm", respectively. In this case, "Example 1" to "Example 3" all obtained battery outputs that are roughly the same as those of these "Comparative Example 6" and "Comparative Example 7". Regarding the deterioration rate of the battery capacity, compared with these "Comparative Example 6" and "Comparative Example 7", "Example 1" to "Example 3" obtained low values ​​indicating an improvement in the deterioration rate.

[0093] In "Example 4" to "Example 6", the Li / M ratio is "1.18". In addition, in these "Example 4" to "Example 6", the density of the negative electrode composite material layer 32N is "1.2 g / cc" similar to the above-mentioned "Example 1" to "Example 3". Furthermore, regarding the amount of lithium contained in the negative electrode composite material layer 32N, "Example 4" is "1000 ppm", "Example 5" is "1280 ppm", and "Example 6" is "1500 ppm". Therefore, in these "Example 4" to "Example 6", the Li / M ratio, the amount of lithium contained in the negative electrode composite material layer 32N, and the density of the negative electrode composite material layer 32N are also values ​​within the above-mentioned appropriate ranges.

[0094] When these "Example 4" to "Example 6" are compared with "Example 1" to "Example 3" having a low Li / M ratio, a higher battery output is obtained. Furthermore, when these "Example 4" to "Example 6" are compared with "Comparative Example 8" and "Comparative Example 9", the Li / M ratio and the density of the negative electrode composite material layer 32N of "Comparative Example 8" and "Comparative Example 9" are equal to those of "Example 4" to "Example 6", and on the other hand, the amount of lithium contained in the negative electrode composite material layer 32N is set to "0 ppm" and "600 ppm", respectively. In this case, "Example 4" to "Example 6" all obtained battery outputs that are roughly the same as those of these "Comparative Example 8" and "Comparative Example 9". Regarding the deterioration rate of the battery capacity, compared with these "Comparative Example 8" and "Comparative Example 9", "Example 4" to "Example 6" obtained low values ​​indicating an improvement in the deterioration rate.

[0095] The Li / M ratio of "Example 7" is "1.20". In addition, the density of the negative electrode composite material layer 32N of "Example 7" is "1.2 g / cc" similar to "Example 1" to "Example 6" described above. Furthermore, the amount of lithium contained in the negative electrode composite material layer 32N is "1000 ppm" similar to "Example 1" and "Example 4". Therefore, the Li / M ratio of "Example 7", the amount of lithium contained in the negative electrode composite material layer 32N, and the density of the negative electrode composite material layer 32N are also values ​​within the above-mentioned appropriate ranges.

[0096] When "Example 7" is compared with "Example 1" to "Example 6" having a low Li / M ratio, a higher battery output is obtained. Furthermore, "Example 7" is compared with "Comparative Example 10" to "Comparative Example 14" and "Comparative Example 15" having the same Li / M ratio and the amount of lithium contained in the negative electrode composite material layer 32N being set to "0 ppm" and "600 ppm", respectively. In this case, "Example 7" obtains a battery output that is substantially the same as that of these "Comparative Examples 10" to "Comparative Examples 14" and "Comparative Example 15". Regarding the degradation rate of the battery capacity, "Example 7" obtains a low value indicating an improvement in the degradation rate compared with these "Comparative Examples 10" to "Comparative Examples 14" and "Comparative Example 15".

[0097] The Li / M ratios of "Example 8" to "Example 10" are all "1.20" like "Example 7". In addition, in "Example 8" to "Example 10", the amount of lithium contained in the negative electrode composite material layer 32N is "1280 ppm". Furthermore, regarding the density of the negative electrode composite material layer 32N, "Example 8" is "1.1 g / cc", "Example 9" is "1.2 g / cc", and "Example 10" is "1.4 g / cc". Therefore, the Li / M ratios of these "Example 8" to "Example 10", the amount of lithium contained in the negative electrode composite material layer 32N, and the density of the negative electrode composite material layer 32N are also values ​​within the above-mentioned appropriate ranges.

[0098] These "Example 8" to "Example 10" also obtained battery outputs that were substantially equivalent to that of "Example 7" (the Li / M ratio of "Example 7" was equal to that of "Example 8" to "Example 10"). Moreover, regarding the degradation rate of the battery capacity, compared with "Example 7" in which the amount of lithium in the negative electrode composite material layer 32N was small, these "Example 8" to "Example 10" obtained low values ​​indicating an improvement in the degradation rate.

[0099] The Li / M ratios of "Example 11" to "Example 13" are all "1.20" like "Example 7" to "Example 10". In addition, the amount of lithium contained in the negative electrode composite material layer 32N of these "Example 11" to "Example 13" is "1500 ppm". Furthermore, regarding the density of the negative electrode composite material layer 32N, "Example 11" is "1.1 g / cc" like "Example 8", "Example 12" is "1.2 g / cc" like "Example 9", and "Example 13" is "1.4 g / cc" like "Example 9". And, therefore, the Li / M ratios of these "Example 11" to "Example 13", the amount of lithium contained in the negative electrode composite material layer 32N, and the density of the negative electrode composite material layer 32N are also values ​​within the above-mentioned appropriate ranges.

[0100] These "Example 11" to "Example 13" also obtained battery outputs that were substantially equivalent to those of "Example 7" to "Example 10" (the Li / M ratios of "Example 7" to "Example 10" were equal to those of "Example 11" to "Example 13"). Moreover, regarding the degradation rate of the battery capacity, compared with "Example 7" to "Example 13" in which the amount of lithium in the negative electrode composite material layer 32N was small, these "Example 11" to "Example 13" obtained low values ​​indicating an improvement in the degradation rate.

[0101] In addition, the comparison was made between Examples 8 to 10, Comparative Example 16, and Comparative Example 17, in which the Li / M ratio and the amount of lithium in the negative electrode composite material layer 32N were equal to each other. In this case, the degradation rate of Examples 8 to 10 and Comparative Example 16, in which the density was "1.4 g / cc" or less, was improved compared to Comparative Example 17, in which the density of the negative electrode composite material layer 32N was "1.6 g / cc". Furthermore, the comparison was made between Examples 11 to 13, Comparative Example 18, and Comparative Example 19, in which the Li / M ratio and the amount of lithium in the negative electrode composite material layer 32N were equal to each other. In this case, the degradation rate of Examples 11 to 13 and Comparative Example 18, in which the density was "1.4 g / cc" or less, was also improved compared to Comparative Example 19, in which the density of the negative electrode composite material layer 32N was "1.6 g / cc".

[0102] In this way, for the Li / M ratio, the amount of lithium contained in the negative electrode composite material layer 32N, and the density of the negative electrode composite material layer 32N, respectively, which are within the above-mentioned appropriate ranges, "Example 1" to "Example 13", the effect of improving the battery output and extending the life is obtained. In addition, it is also confirmed from the verification results that the negative electrode composite material layer 32N contains lithium in an amount of more than 1000ppm and less than 1500ppm. The density of the negative electrode composite material layer 32N is more than 1.1g / cc and less than 1.4g / cc. The Li / M ratio of the lithium transition metal oxide contained in the form of a positive electrode active material in the positive electrode composite material layer 32P is more than 1.16 and less than 1.20. It is confirmed that it is appropriate to combine the above factors into its preferred range.

Claims

1. A lithium-ion secondary battery, comprising an electrode body formed by stacking an electrode sheet on a positive electrode side and an electrode sheet on a negative electrode side with a separator interposed therebetween, wherein each electrode sheet is formed by coating an electrode composite material onto a substrate as a current collector, and the facing surface of the negative electrode composite material layer in the electrode sheet on the negative electrode side is larger than the facing surface of the positive electrode composite material layer in the electrode sheet on the positive electrode side, wherein: The negative electrode composite material layer contains lithium in an amount of 1000 ppm or more and 1500 ppm or less in advance, and The density of the negative electrode composite material layer is greater than or equal to 1.1 g / cc and less than or equal to 1.4 g / cc. The positive electrode composite material layer includes a lithium transition metal oxide as a positive electrode active material, and the ratio of the number of lithium atoms (Li) in the lithium transition metal oxide to the sum of the number of transition metal atoms (M), that is, the Li / M ratio, is 1.16 or more and 1.20 or less.

2. The lithium ion secondary battery according to claim 1, wherein The lithium previously contained in the negative electrode composite material layer is derived from the carboxymethyl cellulose-lithium salt contained in the negative electrode composite material that forms the negative electrode composite material layer by the coating.

3. The lithium ion secondary battery according to claim 2, wherein: The negative electrode composite material includes 0.4 wt % or more and 0.6 wt % or less of the carboxymethyl cellulose-lithium salt.

4. The lithium ion secondary battery according to any one of claims 1 to 3, wherein The lithium transition metal oxide contained in the positive electrode composite material layer is LiNi x Co y Mn z O2, where x+y+z=1, 0 <x<1,0<y<1,0<z<1。 5. The lithium ion secondary battery according to any one of claims 1 to 3, wherein The negative electrode capacity / positive electrode capacity ratio of the electrode sheet on the positive electrode side and the electrode sheet on the negative electrode side is 1.6 or more and 1.8 or less.

6. The lithium ion secondary battery according to any one of claims 1 to 3, wherein The end area of ​​each electrode sheet where the electrode composite material is not applied to the substrate is regarded as an uncoated portion of the electrode sheet. The electrode sheet on the negative electrode side has the end region in which the width of the uncoated portion is 300 μm or less.

7. The lithium ion secondary battery according to any one of claims 1 to 3, wherein The separator has a porosity of 50% or more and 60% or less.

Citation Information

Patent Citations

  • Nonaqueous electrolyte secondary battery

    JP1995192766A

  • Wound type nonaqueous lithium power storage element

    JP2018056412A